Do incidente de resolução de demandas repetitivas como mecanismo de formação concentrada de precedentes: um olhar a partir dos julgados do Tribunal Regional Federal da 5ª região. - Novais, Mateus Pereira de Carvalho (2024)
Given the novelty introduced by the Civil Procedure Code of 2015, the repetitive claims resolution incident appears as a procedural technique for the solution, with the power of obligatory precedent, of questions related to repetitive causes. This research will comprise, through a hypothetical-deductive method, the systematized study of the main aspects of the incident, disposing, at first, regarding the repetitive demands and its main nuances in Brazil, and, posteriorly, about its admissibility requirements. In addition, it will consist of a qualitative analysis carried out through a case study of some of the suits of the incident that were processed before the Federal Regional Court of the 5th Region, with the primary purpose of observing how the said Court has molded its structures to conceive it, in a comparative appreciation between what has occurred in forensic practice and what the procedural codification advocates.